Estratégias de manejo para otimização da rizogênese adventícia e qualidade de mudas clonais de eucaliptos subtropicais - Griebeler, Adriana Maria (2023)
Forest genetic improvement has advanced in the development of subtropical Eucalyptus clones and hybrids. However, some materials have low percentages of adventitious rooting (E%) and quality of the root system. This fact limits the production of seedlings by minicutting, as well as the expansion of the portfolio of operational clones in the nurseries and, consequently, the expansion of commercial plantations to places with climatic limitations. Thus, the objective of the present study was to define management strategies to optimize adventitious rhizogenesis and quality of clonal seedlings of Eucalyptus benthamii Maiden et Cambage, Eucalyptus dunnii Maiden and the hybrid Eucalyptus urophylla S.T. Blake x Eucalyptus dunnii Maiden. From this, the present thesis was structured in three chapters. The experiments were carried out in a greenhouse at the forest nursery of the company CMPC – Celulose Riograndense located in Barra do Ribeiro, RS. In Chapter 1, the effects of using a mini-tunnel in the clonal mini-garden (MG) on environmental variables, ecophysiological and productive aspects of mini-stumps, as well as the morphology and E% of mini-cuttings of clones of E. benthamii (B1 and B2), E. dunnii (D1 and D2) and the hybrid E. urophylla x E. dunnii (UD), during the four seasons in southern Brazil. The obtained results expressed variations in the responses between the clones and the periods of conduction of the experiments. The use of the minitunnel in the MG changes the environmental conditions and consequently improves the ecophysiological characteristics of the ministumps, increasing rooting during winter and spring. Chapter 2 aimed to verify the influence of using a mini-tunnel in the MG, associated with different rooting environments, on the survival, rhizogenesis and morphological attributes of seedlings of different clones, produced during the spring-summer and autumn-winter periods. It was found that during autumn-winter the use of minitunnel and red screen in the greenhouse allowed greater rooting for clones D2 (E > 82%) and UD (E > 76%), expressing their potential as possible operational clones. In Chapter 3, the effect of applying different concentrations of Acacia mearnsii De Wild. pyroligneous extract (EP) was evaluated on rooting and seedling quality of the studied clones, during summer and winter. There was a positive effect of foliar spraying of intermediate concentrations (3.5% to 4.5%) on the E% and quality of the produced seedlings. Thus, the EP of A. mearnsii is shown to be a potential sustainable input to optimize the E% of clones that are difficult to propagate, in addition to contributing to a greater allocation of dry matter to clonal seedlings of Eucalyptus spp.